THE USE OF STORYTELLING IN TEACHING ENGLISH AS A FOREIGN LANGUAGE (EFL) - Musaxonova Shahzoda Hasan qizi; Zubaydova Nilufar Neʼmatullayevna; Azzamova Nigora Rajabboyevna (TADQIQOTLAR.UZ, 2024)
One of the special methods for teaching foreign languages to kids of any age is the use of stories. It gives the instructor the opportunity to interact directly with the audience and build strong emotional bonds with students, which helps the tale stick in their minds for a long time. Listeners may easily and naturally learn communication skills through storytelling. This essay assesses the efficacy of the storytelling strategy and examines how it affects the growth of language proficiency in foreign language instruction.